1989
DOI: 10.1164/ajrccm/140.4.1021
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishable Sensations of Breathlessness Induced in Normal Volunteers

Abstract: Various theories about the genesis of dyspnea have often assumed that the sensation is similar from patient to patient and is generated by a single underlying mechanism. To investigate whether breathlessness induced in normal volunteers by different stimuli represents one or more than one sensation, we studied 30 subjects in whom breathlessness was induced by each of 8 different stimuli: breath-holding, CO2 inhalation, inhalation of CO2, with ventilation voluntarily targeted below the level dictated by chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
150
0
12

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(166 citation statements)
references
References 9 publications
4
150
0
12
Order By: Relevance
“…Defined by the American Thoracic Society as 'a subjective experience of breathing discomfort that consists of qualitatively distinct sensations that vary in intensity', dyspnoea is a very personal experience (ATS, 1999). Descriptions vary widely; examples include 'short of breath', 'hard to move air', 'chest tightness', 'choking', 'panting', and 'gasping' (Brown et al, 1986;Simon et al, 1989;Roberts et al, 1993;Harver et al, 2000). The experience of dyspnoea can be affected by many conditions, including the cancer itself, coexisting diseases, and cancer cachexia (Reuben and Mor, 1986;Ripamonti, 1999;Bruera et al, 2000).…”
mentioning
confidence: 99%
“…Defined by the American Thoracic Society as 'a subjective experience of breathing discomfort that consists of qualitatively distinct sensations that vary in intensity', dyspnoea is a very personal experience (ATS, 1999). Descriptions vary widely; examples include 'short of breath', 'hard to move air', 'chest tightness', 'choking', 'panting', and 'gasping' (Brown et al, 1986;Simon et al, 1989;Roberts et al, 1993;Harver et al, 2000). The experience of dyspnoea can be affected by many conditions, including the cancer itself, coexisting diseases, and cancer cachexia (Reuben and Mor, 1986;Ripamonti, 1999;Bruera et al, 2000).…”
mentioning
confidence: 99%
“…(6)(7)(8)(9) Figure 1 -Dendrogram illustrating the distribution of dyspnea descriptors and clusters formed after 180 volunteers had selected the three descriptors that best described their sensation of dyspnea. criterion on which to base the decision depends on the point of view and judgment of authors.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a study of healthy volunteers submitted to eight distinct respiratory stimuli, such as carbon dioxide inhalation, breathing against elastic load, and physical exercise, the authors identified clusters of descriptive terms applied to the respiratory sensations; those clusters were associated with the different agents employed. (6) In another study, involving 218 patients presenting with seven distinct cardiorespiratory conditions in the stable phase, the use of a questionnaire including 15 descriptive questions regarding their respiratory sensations revealed clusters of descriptors, the combinations of which were specific to each diagnosis. (9) Although there have been many studies regarding the potential use of descriptive terms applied to the sensation of dyspnea (dyspnea descriptors), (11)(12)(13)(14)(15)(16) there is a lack of such studies in Brazil.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations